B-Mode and pulsed Doppler sonography of kidney in healthy sheep according to age - Santarosa, Bianca P. [UNESP]; Ferreira, Danilo O.L.; Belotta, Alexandra F. [UNESP]; Dias, Adriano [UNESP]; Mamprim, Maria J. [UNESP]; Gonçalves, Roberto C. [UNESP] (FapUNIFESP (SciELO), 2016)
There is no standardization in the literature of kidney length in sheep at different ages, as there are few studies about the access with the Doppler triplex ultrasound for the renal vascularization in this species. Eighty healthy sheep of three age groups of Ile de France and White Dorper breed were used: 20 lambs, 30 yearlings and 30 adults (8 rams and 22 ewes). Renal healthiness of the animals was confirmed by serum biochemical tests of urea and creatinine, and by observation of renal architecture with conventional ultrasound, besides measurement of vital parameters. A portable ultrasound (My LabTM30 Vet Gold Esaote®, Esaote Healthcare) device was used, with a convex transducer with 3.5MHz frequency. After identification of the kidneys in two-dimensional mode, the measurement of length in the sagittal section was performed in all sheep (n=80). Then color Doppler was activated for visualization of renal and interlobar arteries of the right kidney, and the resistivity index (RI) of the yearlings (n=30) and ewes (n=22) was measured. Biochemical tests remained within normal limits and renal architecture was preserved. The values of the right and left renal length were different between the groups, increasing with age (4.34cm and 4.31cm in lambs; 6.08cm and 6.23cm in yearlings; 7.57cm and 7.37cm in adults, respectively). Median values of RI of the renal artery were statistically different (p < 0.05) between the groups of yearlings (0.57) and ewes (0.52). The median RI of the interlobar artery was similar in yearlings (0.58) and ewes (0.54).
Keywords: Creatinine doppler; Kidneys; Sheep; Ultrasonography